Nanodiamonds: a critical component of anodes for high performance lithium-ion batteries. Issue 69 (4th August 2016) - Song, Yanpeng; Li, Hongdong; Wang, Liying; Qiu, Dongchao; Ma, Yibo; Pei, Kai; Zou, Guangtian; Yu, Kaifeng
Abstract : Detonation nanodiamonds (DNDs) are deposited on graphene nanosheets (GNSs) to form a hybrid DND/GNS anode material for improving the performance of lithium ion batteries with a high lithium storage capacity and excellent cycling performance and stability. Abstract : Detonation nanodiamonds (DNDs) have been introduced into a carbonaceous anode for improving the performance of lithium ion batteries (LIBs). The lithium storage capacity, cycling performance and stability of the LIBs are increased and this is related to the DNDs' unique characteristics of chemical inertness, a larger surface area, low expansion, and high lithium adsorption capacity.